IMPLEMENTATION OF DECISIONINVEST IN CAPITAL MARKET TOLABORATORY OF FINANCIAL AND CAPITAL MARKET STUDY PROGRAM MANAGEMENT - Hasa Nurrohim KP; C. Ambar Pujiharjanto; Sri Isworo Ediningsih (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
This research carried out to look back at investment decisions made by the academic community within the Management Study Program UPN "Veteran" Yogyakarta, both conducted by lecturers, employees and students. The existence of the Financial and Capital Market Laboratory is expected to make it easier for lecturers, employees and students to invest in the form of share ownership. Testing is done by multiple regression by testing the factors of Neutral Information, Accounting Information, Classic, Social Relevance, Advocate Recommendation, Personal Financial Need.